2023
DOI: 10.2196/43126
|View full text |Cite
|
Sign up to set email alerts
|

Extended Family Outreach in Hereditary Cancer Using Web-Based Genealogy, Direct-to-Consumer Ancestry Genetics, and Social Media: Mixed Methods Process Evaluation of the ConnectMyVariant Intervention

Abstract: Background Cascade screening, defined as helping at-risk relatives get targeted genetic testing of familial variants for dominant hereditary cancer syndromes, is a proven component of cancer prevention; however, its uptake is low. We developed and conducted a pilot study of the ConnectMyVariant intervention, in which participants received support to contact at-risk relatives that extended beyond first-degree relatives and encourage relatives to obtain genetic testing and connect with others having … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“… USA Randomized controlled trial, 98 Pancreatic ductal adenocarcinoma Remote genetic education and testing Courtney 21 Impact of free cancer predisposition cascade genetic testing on uptake in Singapore. Singapore Prospective cohort study, 826 Not specified Free cascade testing Chen 64 Extended Family Outreach in Hereditary Cancer Using Web-Based Genealogy, Direct-to-Consumer Ancestry Genetics, and Social Media: Mixed Methods Process Evaluation of the ConnectMyVariant Intervention USA Prospective cohort study, 57 Not specified ConnectMy Variant (Web-based genealogy) Katz 33 Cascade Genetic Risk Education and Testing in Families With Hereditary Cancer Syndromes: A Pilot Study USA Randomized controlled trial, 66 Breast cancer Online cancer genetic education followed by free or paid ($50) testing Goodman 65 Development of a secure website to facilitate information sharing in families at high risk of bowel cancer— The Familyweb Study UK Cross-sectional study, 198 Colon cancer Use of website as a file sharing facility Li 18 Impact of subsidies on cancer genetic testing uptake in Singapore Singapore Prospective cohort study, 235 Not specified Subsidy schemes Schmidlen 24 Use of a chatbot to increase uptake of cascade genetic testing USA Prospective cohort study, 377 Not specified Cascade chatbot Garcia 34 Mechanisms to increase cascade testing in hereditary breast and ovarian cancer: Impact of introducing standardized communication aids into genetic counseling USA Prospective cohort study, 40 Hereditary breast and ovarian cancer Use of communication aids Aeilts 66 The impact of a cascade testing video on recipients' knowledge, cognitive message processing, and affective reactions: A formative evaluation. USA Cross sectional study, 373 Hereditary b...…”
Section: Resultsmentioning
confidence: 99%
“… USA Randomized controlled trial, 98 Pancreatic ductal adenocarcinoma Remote genetic education and testing Courtney 21 Impact of free cancer predisposition cascade genetic testing on uptake in Singapore. Singapore Prospective cohort study, 826 Not specified Free cascade testing Chen 64 Extended Family Outreach in Hereditary Cancer Using Web-Based Genealogy, Direct-to-Consumer Ancestry Genetics, and Social Media: Mixed Methods Process Evaluation of the ConnectMyVariant Intervention USA Prospective cohort study, 57 Not specified ConnectMy Variant (Web-based genealogy) Katz 33 Cascade Genetic Risk Education and Testing in Families With Hereditary Cancer Syndromes: A Pilot Study USA Randomized controlled trial, 66 Breast cancer Online cancer genetic education followed by free or paid ($50) testing Goodman 65 Development of a secure website to facilitate information sharing in families at high risk of bowel cancer— The Familyweb Study UK Cross-sectional study, 198 Colon cancer Use of website as a file sharing facility Li 18 Impact of subsidies on cancer genetic testing uptake in Singapore Singapore Prospective cohort study, 235 Not specified Subsidy schemes Schmidlen 24 Use of a chatbot to increase uptake of cascade genetic testing USA Prospective cohort study, 377 Not specified Cascade chatbot Garcia 34 Mechanisms to increase cascade testing in hereditary breast and ovarian cancer: Impact of introducing standardized communication aids into genetic counseling USA Prospective cohort study, 40 Hereditary breast and ovarian cancer Use of communication aids Aeilts 66 The impact of a cascade testing video on recipients' knowledge, cognitive message processing, and affective reactions: A formative evaluation. USA Cross sectional study, 373 Hereditary b...…”
Section: Resultsmentioning
confidence: 99%
“…Our initial study assessed the acceptability and demand for using social media and networks created by DTC genomic genealogy sites, such as AncestryDNA or 23andMe, to help people with family outreach. Con-nectMyVariant study participants could engage in several outreach activities [17]. Many of these activities, such as sharing results with close relatives, would be considered traditional cascade outreach.…”
Section: Exploring the Uptake Of New Resources For Extended Family Ou...mentioning
confidence: 99%
“…Some participants wanted to help others prevent cancer, but others were motivated primarily by finding out more about their family history [17]. The pilot study found that connecting an individual with someone else who has the same variant increased participation in family outreach activities 2.5-fold [17]. We initially focused on DTC genetic testing, but we found that other factors such as documentary genealogy sharing, encouragement from putative relatives, and simple reminders contributed more to outreach efforts for most families.…”
Section: Exploring the Uptake Of New Resources For Extended Family Ou...mentioning
confidence: 99%
See 2 more Smart Citations